2018
DOI: 10.7150/thno.22502
|View full text |Cite
|
Sign up to set email alerts
|

Surface Enhanced Raman Spectroscopy (SERS) for the Multiplex Detection of Braf, Kras, and Pik3ca Mutations in Plasma of Colorectal Cancer Patients

Abstract: In this paper, we discuss the use of a procedure based on polymerase chain reaction (PCR) and surface enhanced Raman spectroscopy (SERS) (PCR-SERS) to detect DNA mutations.Methods: This method was implemented by first amplifying DNA-containing target mutations, then by annealing probes, and finally by applying SERS detection. The obtained SERS spectra were from a mixture of fluorescence tags labeled to complementary sequences on the mutant DNA. Then, the SERS spectra of multiple tags were decomposed to compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 45 publications
0
44
0
2
Order By: Relevance
“…A recent study reported PIK3CA mutation frequency of 14% in Belgian colorectal cancer patients. Another recent study on Chinese colon cancer patients reported a mutation frequency of 18.94%, and these mutations were more prevalent in the right-side colorectal cancer [48]. Another study also supported this finding but showed no correlation of PIK3CA gene mutations with clinical parameters such as gender, age, cancer stage, or differentiation [49].…”
Section: Prognostic Importance Of Pik3ca Genetic Mutations In Colorecmentioning
confidence: 91%
“…A recent study reported PIK3CA mutation frequency of 14% in Belgian colorectal cancer patients. Another recent study on Chinese colon cancer patients reported a mutation frequency of 18.94%, and these mutations were more prevalent in the right-side colorectal cancer [48]. Another study also supported this finding but showed no correlation of PIK3CA gene mutations with clinical parameters such as gender, age, cancer stage, or differentiation [49].…”
Section: Prognostic Importance Of Pik3ca Genetic Mutations In Colorecmentioning
confidence: 91%
“…Through utilizing this efficient SERS signal enhancement mechanism, this strategy was able to detect as low as 0. silver iron-mediated SERS signal amplification, which was capable of detecting as low as 0.3 × 10 −15 m of miRNA in the buffer. [128] Copyright 2018, Ivyspring. [127] This strategy was sensitive for the detection of 500-1000 copies mL −1 of cancer-associated Epstein-Barr virus DNA in blood circulation.…”
Section: Nanotag-based Detectionmentioning
confidence: 99%
“…In order to incorporate SERS DNA sensors in actual clinical practice, the development of new, highly active, stable and very reproducible plasmonic substrates for SERS measurements is necessary. Therefore, in our opinion, in addition to the development of new strategies for the SERS detection of mutated DNA, a significant amount of basic studies on the development of new materials for SERS measurements must be conducted, especially because a combination of PCR and SERS provides very successful results for multiplexed DNA detection in real samples [123,124].…”
Section: Summary Conclusion and Future Prospectsmentioning
confidence: 99%